2018
DOI: 10.5222/head.2018.088
|View full text |Cite
|
Sign up to set email alerts
|

Non-Pharmacological Methods Used by Cancer Patients for Pain

Abstract: Bu araştırma, kanserli hastaların ağrıyla baş etmede nonfarmakolojik yöntemleri kullanma durumlarının saptanması amacıyla yapıldı. Yöntem: Tanımlayıcı nitelikte yapılan bu çalışma, 123 kanser hastası ile yürütüldü. Araştırmanın verilerinin toplanmasında "Sözel Derecelendirme Ölçeği" ve literatür doğrultusunda araştırmacılar tarafından hazırlanan "Non-farmakolojik Yöntemler Formu" kullanıldı. Bulgular: Araştırmaya katılan hastaların yaş ortalaması 58.17±15.13 olup, %53.7'si kadın, %53.7'si okuryazar-ilkokul mez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…(26) In studies conducted with cancer patients in Turkey, praying is among the most widely used spiritual methods. (27,28) In clinical studies, it has been shown that stress, chronic depression, social support, and other psychological factors can affect the onset and progression of cancer. On the other hand, it has been suggested that loneliness is a risk factor that increases cancer mortality.…”
Section: Discussionmentioning
confidence: 99%
“…(26) In studies conducted with cancer patients in Turkey, praying is among the most widely used spiritual methods. (27,28) In clinical studies, it has been shown that stress, chronic depression, social support, and other psychological factors can affect the onset and progression of cancer. On the other hand, it has been suggested that loneliness is a risk factor that increases cancer mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Pada pasien kanker, spiritualitas sangat bermanfaat untuk menjaga harga diri, meningkatkan makna dan tujuan hidup, memberikan kenyamanan emosional dan memberikan harapan hidup. Penelitian yang dilakukan oleh Genc peneliti asal Turki tahun 2018, yang menyatakan bahwa untuk menghilangkan rasa sakit yang dirasakan pasien kanker, 87% dari pasien berdo'a memohon kesembuhan untuk menghilangkan rasa sakit dan 59,3% membaca Al-Qur'an untuk mengalihkan rasa sakitnya (Genc, 2018). Penelitian ini sejalan dengan penelitian yang dilakukan oleh Abuelgasim di Arab Saudi 2018, terapi komplementer dan alternative yang paling banyak digunakan pasien kanker dalam mengelola rasa sakit atau nyeri adalah berdo'a (95,4%) dan membaca Al-Qur'an (88,1%) selain itu berdo'a dan membaca Al-Qur'an juga digunakan untuk mengendalikan mood atau mengontrol emosi (Abuelgasim et al, 2018).…”
Section: Pembahasanunclassified
“…By stimulating the pituitary gland on the neuroendocrine system, listening to music has an effect on memory and pain, anxiety and perception by increasing the release of endorphins (Arslan & Özer, 2007;Genç et al, 2018). Music, by affecting the mood of the people and sedating, distracts the attention, enables patients to suspend themselves from their pain and is beneficial in reducing pain-intensifying emotions such as anxiety and fear (Arslan & Özer, 2007).…”
Section: Introductionmentioning
confidence: 99%